2014
DOI: 10.1007/s00590-014-1568-z
|View full text |Cite
|
Sign up to set email alerts
|

Is tranexamic acid clinically effective and safe to prevent blood loss in total knee arthroplasty? A meta-analysis of 34 randomized controlled trials

Abstract: Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 46 publications
2
62
1
2
Order By: Relevance
“…The main findings of this metaanalysis have been confirmed in other meta-analyses that included additional trials for TKA, THA, and spine surgery, but several important questions remain unanswered [3,14,15]. For example, additional large observational studies are warranted to resolve uncertainty in the risks for thromboembolic harms, clarify whether certain dosing regimens might be superior to others, investigate use in specific patient populations such as those with contraindications to intravenous tranexamic acid, and investigate efficacy and cost-effectiveness in combination with other perioperative blood management strategies.…”
Section: Take-home Messagessupporting
confidence: 63%
“…The main findings of this metaanalysis have been confirmed in other meta-analyses that included additional trials for TKA, THA, and spine surgery, but several important questions remain unanswered [3,14,15]. For example, additional large observational studies are warranted to resolve uncertainty in the risks for thromboembolic harms, clarify whether certain dosing regimens might be superior to others, investigate use in specific patient populations such as those with contraindications to intravenous tranexamic acid, and investigate efficacy and cost-effectiveness in combination with other perioperative blood management strategies.…”
Section: Take-home Messagessupporting
confidence: 63%
“…The use of TXA in primary TKA is today widely accepted, and several studies and meta-analyses have confirmed the efficacy of TXA at decreasing blood loss without increasing complications and costs [9, 13, 14]. Several clinical trials have identified that intravenous (IV) TXA is effective in reducing perioperative blood loss and the need for subsequent blood transfusions in TKA [15–17].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of TXA in reducing postoperative bleeding has been well established in many previous studies, primarily focused on total joint arthroplasty and spine surgery. [11][12][13][14][15][16][17][18][19] The reduced bleeding potentially allows for faster recovery and better early clinical outcomes. One study reported that TXA improves early functional outcomes of primary total knee arthroplasty.…”
Section: Discussionmentioning
confidence: 99%